2022
DOI: 10.3390/app12125828
|View full text |Cite
|
Sign up to set email alerts
|

Learning Robust Shape-Indexed Features for Facial Landmark Detection

Abstract: In facial landmark detection, extracting shape-indexed features is widely applied in existing methods to impose shape constraint over landmarks. Commonly, these methods crop shape-indexed patches surrounding landmarks of a given initial shape. All landmarks are then detected jointly based on these patches, with shape constraint naturally embedded in the regressor. However, there are still two remaining challenges that cause the degradation of these methods. First, the initial shape may seriously deviate from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…It was found that pause duration and articulation rate, could accurately distinguish between individuals with dementia with an accuracy of 91.5%. Quan et al [51] investigated pitch and energy features for dementia detection. The study resulted in the highest accuracy of 87.3%.…”
Section: ) Dementia Detection For Diverse Populationsmentioning
confidence: 99%
“…It was found that pause duration and articulation rate, could accurately distinguish between individuals with dementia with an accuracy of 91.5%. Quan et al [51] investigated pitch and energy features for dementia detection. The study resulted in the highest accuracy of 87.3%.…”
Section: ) Dementia Detection For Diverse Populationsmentioning
confidence: 99%